Collection management with gender perspective in public libraries of Chile - Gascon-Barcaza, Catalina (2025)
The study characterizes the conceptual and procedural elements to be considered for the management of collections with a gender perspective in public libraries in Chile, within a context lacking national guidelines, as there is no public policy on the matter. It is a descriptive study using a qualitative methodology with a phenomenological approach. The sample is non-probabilistic and intentional. The data collection techniques used were documentary research and semi-structured interviews, while the data analysis technique was qualitative content analysis. The study's results show that the scientific production and local initiatives aimed at managing collections with a gender perspective are insufficient. Therefore, it is necessary to consider various conceptual and procedural elements to develop a methodology that enables the management of collections that respond to the local needs of public library users, through participatory processes that involve different stakeholders in the system, creating strategies to raise awareness among professional and technical staff. Additionally, the need for a national collection management policy for the public library system is emphasized, one that decentralizes the process and addresses the specific needs of each community.